Pengaruh Kedisiplinan Siswa terhadap Kemandirian Belajar Kelas V SDN Gugus 4 Kabupaten Rejang Lebong - Maman Ariansyah; Osa Juarsa; Daimun Hambali (Universitas Bengkulu, 2019)
This study aims to analyze the influence of student discipline on the independence of learning class V SDN Gugus 4 Rejang Lebong Regency. This research is quantitative research. The research method used is survey method with simple linear regression analysis technique. Subjects in this study were students of grade V SDN Gugus 4 Rejang Lebong Regency. The population in this study were all students of class V SDN Gugus 4 Rejang Lebong Regency amounted to 107 students, namely SDN 113 (VA amounted to 23 students and VB totaled 24 students), SDN 12 amounted to 35 students, and SDN 97 amounted to 25 students. The sample in this study were 27 students, namely SDN 113 (VA amounted to 6 students and VB totaled 6 students), SDN 12 amounted to 9 students, and SDN 97 amounted to 6 students. Sampling in research with simple random sampling technique with sampling 25% from population. The research instrument used is a student discipline questionnaire and questionnaire independence learning in the form of statements. The data of this study were analyzed by using simple linear regression analysis. The result of research known that fhitung> ftabel (34,804> 4,225) hence can be concluded that regression equation significant. The result of the test makes the regression equation expressed by equation = 6,787 + 0,884 X. Correlation coefficient value of 0.763 and the value of coefficient of determination (R2) of 0.582 which means that the contribution or amount of influence provided by the discipline of students to learning independence of 58.20%. It can be seen from the result of regression significance test showing significant regression and description of research result indicate that student discipline in class V SDN Gugus 4 Rejang Lebong Regency give good influence to the independence of students learning class V SDN Gugus 4 Rejang Lebong Regency.